Investigating Factors Responsible For Low Chemistry Enrollment: A Case Study University Of Ibadan-Okene Study Centre - Ugwo, Jeremiah; Yusuf , Barnabas O.; Oyedoyin , Oyetunde Samuel (Indonesian Scientific Publication, 2024)
The role of chemistry in the promotion of national development cannot be overemphasized, consequently there is need to put in place all measures to sustain the acquisition of knowledge such as the number of student’s subscription. This study explores the factors influencing the low enrollment of students in chemistry education at tertiary institutions, focusing on the Federal College of Education Okene, in affiliation with the University of Ibadan. The study utilized an opinion survey research design and descriptive research method to systematically investigate the factors influencing chemistry enrollment. The validated questionnaire shows a reliability coefficient of 0.87, using descriptive research methods for data analysis. The population consisted of 120 students, with 40 from the chemistry department and 80 from the biology department selected randomly. A quantitative research approach was employed for data analysis, using the statistical tools of frequency, percentage, mean, and a significance test to make decisions based on the research questions posed. The study signifies challenges in student enrollment and suggests interventions to improve the attractiveness and effectiveness of chemistry education programs.